High-Resolution Diffusion-Weighted Imaging Increases Lesion Detectability in Patients with Transient Global Amnesia - Choi, B.S.; Kim, J.H.; Jung, C.; Kim, S.Y. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: DWI can detect small punctate hyperintense lesions of the hippocampus in patients with TGA. We investigated whether small TGA lesions can be detected more often by increasing the resolution of DWI. MATERIALS AND METHODS: Of 31 consecutive patients with TGA, 27 underwent DWI, twice at the first visit (range 1.5–22 hours; mean 10 hours) and at follow-up (range 50–87 hours; mean 72.5 hours) after the onset of their symptoms. Each DWI included 2 different spatial resolutions with the same b-value (2000 seconds/mm2): conventional resolution in a 128 × 128 matrix with 3-mm section thickness and high resolution in a 220 × 220 matrix with 2-mm section thickness. The number and contrast of hyperintense lesions were compared between the 2 resolutions. RESULTS: Twenty-two of the 27 patients had single or multiple TGA lesions. The total number of lesions detected on conventional and high-resolution DWI was 11 and 22, respectively, at the first visit, and was 24 and 37, respectively, at follow-up. The number of lesions was significantly larger on high-resolution DWI than on conventional resolution at the first visit (P < .01) and at the follow-up (P < .01). Lesion contrast was significantly increased on high-resolution DWI (P < .01). CONCLUSIONS: Higher DWI resolution increased lesion detectability in patients with TGA. Considering the small size of TGA lesions, the resolution of DWI is an important parameter influencing lesion detectability. CIconfidence intervalORodds ratioSENSEsensitivity encodingSIsignal intensityTGAtransient global amnesia